Evaluation of an enzyme immunoassay for IgM antibodies to Treponema pallidum in syphilis in man. Issue 5 (October 1984) - Müller, F; Moskophidis, M
Abstract : An enzyme immunoassay (EIA) for the detection of immunoglobulin M (IgM) antibodies to Treponema pallidum was investigated for specificity and sensitivity. Using the results in serum from 1192 patients with successfully treated syphilis, the assay was calculated to be about 97% specific. As in any other IgM enzyme linked immunosorbent assay (ELISA), rheumatoid factor played an important part in causing false positive results. Pre-absorption of serum with aggregated IgG was therefore necessary to perform the test. Evaluation of the results in serum from 385 patients with untreated primary, secondary, and latent syphilis as well as patients with untreated reinfections showed that the sensitivity of the assay depended on the stage of infection and varied between 98% and 93%. IgM antibody titres were about ten times higher in the EIA than in the indirect immunofluorescence assay using the IgM fractions of serum. From the results it may be concluded that the EIA is an appropriate technique not only for rapid and sensitive measurement of IgM antibodies in most patients with untreated syphilis but also for selecting treponemal IgM non-reactive patients.